Citra Perempuan dalam Tayangan Iklan TV: Citra Perempuan dalam Tayangan Iklan TV - Fathiyah; Nur Fahmi Hidayah (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Advertising is an important part of marketing activities, with the ability of advertising to build the image of a product able to attract the attention of potential consumers. Television advertisements display women in images as sex objects and decoy. Women as sex objects sre displayed in the form of women’s domestic roles, while images as a decoy are displayed in the form of sexual exploitation to attract the attention of consumers.